Evaluasi User Experience Menggunakan User Experience Questionnare (UEQ) (Studi Kasus : Website Bombanakab.go.id) - Fatmawati, Ifan; Fajriani, Alfiah; Razilu, Zila (STKIP PGRI Tulungagung, 2025)
The concept of user experience, which includes users' perceptions of their interactions with digital systems, has emerged as a result of the use of websites as platforms for interaction and communication. This research aims to evaluate user experience on the bombanakab.go.id website. The User Experience Questionnaire (UEQ) method is used to collect data. Data was collected through a questionnaire, which included 26 questions in which six aspects were assessed by 43 respondents. The data is then analyzed using data analysis tools to produce average values, variances, and standard deviations. The research results show that the bombanakab.go.id website received a good rating in most aspects, except for novelty; it did not reach a positive value. In the benchmark test results, aspects of attractiveness (1.60), efficiency (1.58), accuracy (1.52), and stimulation (1.49) reached the good category, while the clarity aspect received a value of 1.36 above average and the novelty aspect (0.58) was in the below average category.